Making their minds up: flux and stability in young children’s career aspirations in North East England - Carol Davenport; Annie Padwick (Humanities & Social Sciences Communications)
Abstract School career information advice and guidance in England has typically focused on pupils aged 13–18. However, pupils aged under 11 have already formed career aspirations. Career aspirations are used as a proxy for future occupational destinations. This study tracks the individual career aspirations over 3 years for 78 children aged 7–9 at the start of study, from three schools in the North East England taking part in a STEM outreach project. The data are also used to explore the applicability of aspiration development frameworks for younger children. The majority of children were able to name at least one career aspiration with nearly 70% naming more, although these aspirations were drawn from a relatively narrow pool of jobs related to children’s interests and jobs they see around them. 38% of the children had the same aspiration over time, but 60% of children changed their careers aspirations completely over the 3 years of the study. Career aspirations were strongly gendered, with boys naming a smaller pool of jobs most often. Between 2019 and 2021, there was an increase in STEM aspirations named by boys, and a decrease by girls. Thematic analysis of the reasons given for different aspirations identified four themes: self-actualisation, altruism, characteristics of the job, and role models. These themes were related to the aspiration frameworks. This study shows that there is both flux and stability in children’s aspirations between the ages of 7 and 11. The gendered career choices at both time points indicate that there is a need for educators to challenge stereotypes about who can do what type of job from a much earlier age. All aspirations were drawn from a relatively small pool of job suggesting that introducing children to a wider range of jobs at an earlier age could support development of aspirations.